퇴원환자의 병원중심 방문영양지도 요구도 조사 - 안수미(Su Mi Ahn) (Korean journal of community nutrition, 2014)
Objectives: The purpose of this study was to provide a basic data of nutrition services in home health care by analyzing hospital-based home-visit nutrition education needs of patients at discharge. Methods: Data was collected from September 11 to October 12, 2012 by administering questionnaires to 289 chronic disease patients to be discharged from a university hospital in Pusan. The home-visit nutrition education instruments used for collecting data were developed by the researcher. Results: Regarding the demands of home-visit nutrition education, 62.3% of subjects were willing to use home-visit nutrition education and 37.7% weren't. The main reason for using the home-visit nutrition education was "the effective nutrient management in consultation with an individual's doctor", 38.9% and 31.2% of patients who did not wish to use the service gave the reason for their decision as, "Just by managing the nutritional requirements of a family's diet and, the patient will be able to fully recover", respectively. As for the demand, classified with the areas of home-visit nutrition education, the demand for the area of basic nutrition (3.75/5.00) was the highest followed by, the area of educational nutrition (3.74/5.00), therapeutic nutrition (3.67/5.00), and dietary nutrition (3.55/5.00). The demand for the area of educational nutrition was high "Considering the state of dietary management, such as disease status and drugs", 73.7%. As for the relation between the characteristics of the study subjects and analysis of demand home-visit nutrition education, the characteristic of subjects, that is, "regular home-visit nutrition education", "practice of diet therapy after discharge" had a significant difference statistically (p < 0.01). As for the relation between the needs for fundamental home-visit nutrition education and the demand of home-visit nutrition education, basic nutrition, educational nutrition, therapeutic nutrition, and dietary nutrition had a significant difference statistically (p < 0.01).